Saint Simeon's Two Bodies: Relics as Political Instruments During the Reign of Louis of Anjou (1342-1382) - Munk, Ana (2004)
This conference presentation explored the two compeeting cults of Saint Simeon, in Venice and Zadar, as well as the artistic representations of Saint Simeon in these two cities: the shrine of Saint Simeon in Zadar and effigy tomb of Saint Simeon in San Simeone Grande in Venice.
ENG